Foreign trade competitiveness analysis of Kazakhstan (Журналистика сериясы, 2016)
The article presents the results of research, which aims to rationale of foreign trade competitiveness indicators in Kazakhstan. The competitiveness of foreign trade of the country determines the location and success of the national products in specific industries and locations that the country takes on the world market and depends primar-ily on the competitiveness of produced goods [1, 255 p.].To address the scientific objectives of the study we demonstrated the quantitative and qualitative development of Kazakh economy sectors and their comparison with other countries, taking into account the objectives set by the state to improve the competitiveness of the country and entry into the top of 50 world countries. The main reason for the study is that the foreign trade structure of the country is dominated by import, and export is mainly focused on com-modities. Development of export potential by increasing the share of non-primary goods will increase the competitiveness of foreign trade in global markets.